A dual-function chitosan packaging film for simultaneously monitoring and maintaining pork freshness. (30th October 2022) - Lin, Wanmei; Huang, Gengli; Yang, Weixia; Zeng, Shuhao; Luo, Xueli; Huang, Jihong; Li, Zhonghong
Graphical abstract: Highlights: The synthesized N-doped carbon dots (N-CDs) had a pH sensing ranging from 4.0 to 8.0. N-CDs remained fluorescent property after being loaded to chitosan (CS) film matrix. Hydrogen bonds were formed between CS and N-CDs. Antioxidant and antibacterial properties of pristine CS films was improved by N-CDs. Cell viability and hemolytic activity test proved that CS/N-CDs film was safe. Abstract: Exploring food packaging films simultaneously possess freshness monitoring and maintaining can effectively tackle food safety issues. Here, we constructed a chitosan/N-doped carbon dots (CS/N-CDs) film which can monitor the freshness of pork based on pH-mediated fluorescent sensing and extend the shelf life based on the antioxidant, antibacterial and UV shielding properties. The fluorescent intensity of CS/N-CDs films increased with the increase of pork pH from 5.77 to 6.84 which positively related to the change of TVB-N from 6.68 to 17.53 mg/100 g. CS/N-CDs films had a maintaining effect on pork freshness corroborated by the scavenging activity on DPPH and ABTS radicals and antibacterial efficiency and inhibition zones of S. aureus and E.coli, and the total viable count, a value, weight loss, hardness and springiness of pork. Cell viability and hemolytic activity assay proved that CS/N-CDs films was safe. A novel chitosan-based intelligent and active food packaging film was provided.